New Insights into the Role of Crystalline Fe 3 P in Phosphatized Zerovalent Iron for Enhancing Advanced Oxidation Processes and Storage Stability - Wang, Xinhua; Zhang, Peng; Wang, Wenjiang; Rončević, Srd An D; Sun, Hongwen (Environmental science & technology, 2025)
Zerovalent iron (ZVI) is a widely utilized remediation agent for contaminated soil and groundwater; however, it has consistently faced the challenge of balancing catalytic activity with storage stability. Herein, submicron ZVI particles were phosphatized to produce phosphatized ZVI (P-ZVI), which was employed to activate peroxydisulfate (PDS) for phenol degradation. As anticipated, phosphatization significantly enhanced both the storage stability (>10 months vs 1 d) and catalytic activity (4.37 vs 0.12 L m h ) of ZVI compared to unphosphatized counterparts attributed to the formation of a crystalline Fe P shell on P-ZVI. This Fe P shell selectively interacts with H O/O /PDS, maintaining the stability of P-ZVI under high humidity and oxygen conditions while creating mass transfer channels that enhance reactivity in the presence of PDS. Characterization results from the reaction process demonstrated that the Fe P shell activated PDS through both direct (via Fe cations) and indirect pathways (through a phosphorus anion-mediated Fe /Fe cycle), generating reactive species and facilitating mass transfer between core Fe and external PDS for efficient PDS activation and phenol degradation. This study elucidates how constructing an Fe P shell can realize selective activation of PDS while simultaneously enhancing both the storage and catalytic stabilities of ZVI, thereby boosting the practical application of PDS-based advanced oxidation processes in various environmental remediation.